HAKIKAT PEMEROLEHAN BAHASA - Fajerina Eka Az-Zahra; Naila Saadah Ramadhani; Silvina Noviyanti (STKIP Subang, 2024)
This research was motivated by first language acquisition and second language acquisition in children. This research aims to deepen our knowledge of Language acquisition and Language learning. The formulation ofthe problem used in thisstudy includes the nature of language acquisition, differences in language acquisition and language learning in children and their stages, and the mechanism of language acquisition. The research method used is qualitative descriptive with a literature study approach. Data in this study is obtained through journals, articles, or books related to the research topic. The result of this study is that language acquisition is often associated with the first language or also called the mother tongue. While language learning is often associated with a child's second language, which is a new language that children acquire afterthey acquire theirfirstlanguage. In addition,this study also discusses the mechanism of language acquisition which consists of imitation, conditioning, and social cognition mechanisms.